Supply Balance Air Bersih Dan Potensi Nilai Ekonomi Pada Lubang Pasca Tambang Batu Kapur PT Semen Baturaja Tbk - Sari, Enda Kartika; Lindawati; Purry Widiarko (The Manager Review, 2025)
PT Semen Baturaja Tbk. in 2030. The limestone mining area will leave a mine hole covering an area of ​​approximately 78.94. This research aims to determine the volume of water available in the limestone mine void at the end of mining and the supply balance of clean water along with the potential value economy, as well as the quality of water sourced from ex-mining land to residents in the West Baturaja District, Ogan Komering Ulu Regency. Calculations and data analysis use calculations of the catchment area and the area of ​​the mine hole that will be flooded with water, calculation of the volume of water and its potential economic value at PT Semen Baturaja (Tbk) post-mining in 2030, projected water needs and water quality analysis. The research results showed that the total water reserves in PT's post-mining ponds. Semen Baturaja Tbk in 2030 is 23,271,590.10 m3 or 23,271,590.10 liters which will inundate post-mining ponds from an elevation of -20 meters above sea level to +40 meters above sea level. From the results of calculations and projections regarding population growth and water needs, the water reserves in post-mining land ponds in 2030 can meet the water needs of residents in the villages of Laya, Saung Naga, Tanjung Agung, Talang Jawa, Air Gading, Pusar, and Batu Yellow and the volume of water in post-mining land remains stable. Meanwhile, from the aspect of water quality, management needs to be carried out before the water is distributed to the community using filtration or aeration to reduce the value of the Iron (Fe) parameter and also after it reaches customers, the water still has to go through a boiling process first if it is to be consumed.